Solve the following expression:
If
Solve the following expression:
If
Note that we have two unknowns, a and b, and we are also given values for them,
Therefore, let's start by substituting these values in the equation instead of the unknowns:
8*2-1/3*(7+2)=
When there is a number before parentheses, it's like having a multiplication sign between them.
Let's start solving according to the order of operations, beginning with the parentheses:
8*2-1/3*(9)=
Now let's continue with multiplication and division:
16-9/3=
16-3=
13
And that's the solution!